Newborn DNA-methylation, childhood lung function, and the risks of asthma and COPD across the life course. Issue 4 (4th April 2019) - den Dekker, Herman T.; Burrows, Kimberley; Felix, Janine F.; Salas, Lucas A.; Nedeljkovic, Ivana; Yao, Jin; Rifas-Shiman, Sheryl L.; Ruiz-Arenas, Carlos; Amin, N.; Bustamante, Mariona; DeMeo, Dawn L.; Henderson, A. John; et al.
Rationale: We aimed to identify differentially methylated regions (DMRs) in cord blood DNA associated with childhood lung function, asthma and chronic obstructive pulmonary disease (COPD) across the life course. Methods: We meta-analysed epigenome-wide data of 1688 children from five cohorts to identify cord blood DMRs and their annotated genes, in relation to forced expiratory volume in 1 s (FEV1 ), FEV1 /forced vital capacity (FVC) ratio and forced expiratory flow at 75% of FVC at ages 7–13 years. Identified DMRs were explored for associations with childhood asthma, adult lung function and COPD, gene expression and involvement in biological processes. Results: We identified 59 DMRs associated with childhood lung function, of which 18 were associated with childhood asthma and nine with COPD in adulthood. Genes annotated to the top 10 identified DMRs were HOXA5, PAOX, LINC00602, ABCA7, PER3, CLCA1, VENTX, NUDT12, PTPRN2 and TCL1A . Differential gene expression in blood was observed for 32 DMRs in childhood and 18 in adulthood. Genes related with 16 identified DMRs were associated with respiratory developmental or pathogenic pathways. Interpretation: Our findings suggest that the epigenetic status of the newborn affects respiratory health and disease across the life course. We identified 59 differentially methylated regions in cord blood associated with childhood lung function, of which up to 30% were associated with later-life asthma and COPD. The newborns' epigenetic status might affect respiratory health later in life. http://ow.ly/Vvkh30nlF5l